PERILAKU POLITIK MASYARAKAT DALAM PEMILIHAN UMUM (PEMILU) LEGISLATIF KABUPATEN (Studi Kecamatan Dayun, Dapil II Kabupaten Siak, Tahun 2014) - Rizki Rahman Harahap; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This Research aims to determine how political behavior of society particularly in the use of voting rights and choice behaviour of society districts dayun in the legislative elections in 2014 period 2014-2019. This study uses qualitative descriptive approach. Sources of data in this research are human (respondent), and the other documents that support this research. Mechanical footage used in this research is purposive. Data collection using interviews and documentation Based on the research results, it can be concluded first, the political behavior of the community in the district legislative elections can be seen (1) the change of the public choose, it can be seen from the growing number of voters of society with the same respondents compared to the previous election period, (2) political education soecity especially in the election was better, based on public awarness to use their voting right by their desire. Second, in the election procces there are foir indicators became ratings, that is Sociological Factors, Psychological Factors, The Rationsl Choice Factors and the last is Marketing Factors. Based on legislative election in districs Dayun on the period of 2014-2019 that the seocity focused to Sociological Factors by sub indicators ethnicity owned between voter and legislative candidates. Keyword : Political Behaviour, voter in the legislative election